History and historiography of post-Mongol Central Asia and the Middle East studies in honor of John E. Woods - Pfeiffer, Judith; Quinn, Sholeh Alysia (Harrassowitz, 2006)
This book envisioning the Mongol conquests in some Sufi accounts from the 14th to 17th centuries.